Emerging spaces of neoliberal urbanism in China: Land commodification, municipal finance and local economic growth in prefecture-level cities. (November 2015) - Lin, George CS; Zhang, Amy Y
This study examines the popular practices of Chinese urbanism in which commodification of urban land has been actively pursued by municipal governments as a means of revenue generation in the era of neoliberalisation. The research identifies a complex, diverse and self-conflicting internal dynamics that characterised the Chinese state, reveals the political and financial motives of local governments to engage in urbanism and maps out the emerging geography of neoliberal urbanism. Land commodification has become a main source of municipal finance accounting for over 30% of total municipal budgetary revenue and nearly 40% of the fund for urban maintenance and construction. An inverse U-shaped relationship is found between the importance of land commodification to municipal finance and the level of urban economic growth. A similar relationship is identified for land-based municipal finance and degree of openness.